The Use of Clay as Potassium Permanganate Carrier to Delay the Ripening of Raja Bulu Banana - Edi Santosa; Winarso D. Widodo; , Kholidi (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThe objective of this experiment was to study the usage of clay as potassium permanganate (KMnO4) carrier during storage of banana var. Raja Bulu. A 1,000 g air-dried-clay was incorporated well with 500 ml aquadest, added with 100 ml KMnO4 solution (75 %) made into paste. After air dried for 24 hours and then the powder was put in cheese cloth. Three different amount of clay powder were used as treatment, i.e., 10 g, 30 and 50 g for six fingers of banana with three replicates. Results showed that clay powder effective as KMnO4 carrier for storage of banana var. Raja Bulu. Level of clay powder 30 and 50 g significantly increased banana shelf life as indicated by skin color and hardness by 18 days after treatments, as compared to the control. Application of 30 g clay powder resulted in optimum banana storage as compared to other treatments. This experiment indicates that clay powder is promising as KMnO4 carrier.Key words: absorber, clay powder, post harvest, potassium permanganate, Raja Bulu